Ulipristal acetate before high complexity endoscopic (hysteroscopic, laparoscopic) myomectomy – a mini-review - Baranowski, Włodzimierz (Menopause Review/Przegląd Menopauzalny, 2016)
Uterine myomas (fibromas, leiomyomas) are the most common tumours in women, and their clinical signs and symptoms are presented by 25-40% of patients with these benign tumours. According to current guidelines, the armamentarium for myoma management consists of: medical therapy (GnRH, SPRMs), non-surgical alternatives including uterine artery embolisation (UAE), vaginal temporary occlusion of uterine arteries using clamp-like device or MRgFUS technique, and surgical treatment (including minimally invasive techniques). In cases of submucous myomas STEPW classification correlates very well with the risk of incomplete hysteroscopic myomectomies. According to limited literature data, ulipristal acetate as a pre-treatment seems to be very prudent in high complexity hysteroscopic myomectomy (STEPW II, score 5-6). In patients with large uterine myomas (FIGO type 3, 4, 5) undergoing laparoscopic myomectomy, three-month pre-treatment with ulipristal acetate before laparoscopy is feasible and can be recommended because of shorter time of surgery, lower intraoperative blood loss, lower haemoglobin drop, and low postoperative blood transfusion rate.